Evaluation of implantable glucose enzyme-based sensors with extracorporal blood shunt - Tallagrand, T.; Sternberg, R.; Reach, G.; Thevenot, D.R. (Hormone and Metabolic Research, 1988)
This paper presents several methods and instruments developed for the characterization of enzymatic membranes and enzyme electrodes. 1. amplitude and response time of steady-state and transient responses to glucose, automatically determined with an Apple II based workstation; 2. enzyme electrode response to in vitro simulated I.V.G.T.T. and to in vivo I.V.G.T.T. when connected to an extracorporal blood shunt of conscious rats.
Citation Key Alias: tallagrandEvaluationImplantableGlucose1988